The application of the constructivist approach in amtsilati learning in PP. Mambaul Falah - Roisyah, Hannina; Rosidi, Ahmad (At- Ta'lim : Jurnal Pendidikan, 2024)
Difficulties in reading the word are one of the problems faced by students. Because of these difficulties, many students have difficulty reading the yellow book and make many mistakes in memorizing the position of sentences and memorizing a fashol contained in it. The focus of this study is to evaluate the application of the constructivist approach in the pre-learning stage, the process/core learning aspect, and the closing aspect of amtsilati learning. This study uses a qualitative methodology approach that combines descriptive techniques with data collection from observations, interviews, and documentation. The study's findings show that applying the constructivist approach to amtsilati learning is going well. It can be seen through the student's ability to find solutions to a problem, students who are more active than ustad/ustadzah, who only guide and support learning by acting as motivators, facilitators, and assessors.